A cobalt-free positive electrode material and its modification method and application
By modifying the amino groups on the surface of the cobalt-free positive electrode material, the problems of high gas production and poor circulation performance during the battery cycle are solved, and the high cycle stability and thermal stability of the battery are achieved.
Patent Information
- Application Number
- CN202210100957.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-27
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-01-27
AI Technical Summary
The existing cobalt-free cathode material has high gas production and poor circulation performance during the battery circulation process, resulting in low battery safety performance.
By modifying amino groups on the surface of the cobalt-free positive electrode material, an electron cloud polarization region is formed, the migration of lithium ions is promoted, and the formation of SEI film is accelerated, thereby improving the decomposition potential and stability of the electrolyte.
It significantly reduces the gas production of the battery during the circulation process, improves the cycle stability and thermal stability of the battery, and improves the safety performance of the battery.
Smart Images

Figure CN114497532B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cobalt-free materials, and relates to a cobalt-free cathode material, a modification method thereof, and an application thereof. Background Art
[0002] In recent years, the development of the power battery market has entered the fast lane. As a currently most reasonable energy storage medium, the demand for lithium-ion secondary batteries has increased explosively. With the continuous improvement of production capacity, the demand for metal materials has been continuously increasing, especially for cobalt. Its price has nearly tripled from January 2018 to January 2021, resulting in an increasing battery price. Developing cobalt-free cathode materials shows strong application prospects.
[0003] It should be noted that both cobalt-free cathodes and ternary materials are accompanied by the risk of gas generation during the battery cycle, which seriously affects the actual application value of the cathode material. If the cathode material has good compatibility with the electrolyte, this will help reduce the structural damage of the cobalt-free cathode material during the battery cycle and the gas generation risk of the battery. Currently, the conventional method for reducing gas generation in cathode materials is mainly the coating of metal oxides. Although this method is effective, the effect of reducing gas generation is limited.
[0004] CN111916697A discloses a cobalt-free cathode material, a preparation method thereof, a lithium-ion battery cathode, and a lithium battery. The cathode material includes a core and a shell coating the core. The core is a cobalt-free cathode material, and the chemical formula of the core is LiNi x Mn y O 2 , where 0.55 ≤ x ≤ 0.95, 0.05 ≤ y ≤ 0.45. The shell is a coating agent and carbon. The material prepared in this article has poor cycling performance, resulting in an increase in battery gas generation and a reduction in safety performance.
[0005] CN112786834A discloses a positive electrode sheet and a lithium-ion battery including the same. The positive electrode sheet includes a positive electrode material layer. The positive electrode active material in the positive electrode material layer includes a cobalt-free binary material and a ternary single crystal material. The chemical formula of the cobalt-free binary material is LiNi x Mn 1-x O 2 , 0.5 < x < 0.8. The chemical formula of the ternary single crystal material is LiNi a Co b Mn 1-a-b O 2 , 0.5 < a < 0.8, 0.03 < b < 0.3. The particle size of the ternary single crystal material is smaller than that of the cobalt-free binary material. Doping the ternary single crystal material in the cobalt-free material has a high cost.
[0006] CN112186158A discloses a positive electrode composite material, which includes a cobalt-free positive electrode material and a composite carbon coating layer formed on the surface thereof. The particle size of the cobalt-free positive electrode material is 3 to 5 μm, and the cobalt-free positive electrode material with a particle size within this range is more conducive to composite carbon coating. Selecting graphene in the composite carbon can effectively improve the ionic conductivity of the cobalt-free positive electrode material. The positive electrode composite material can also effectively isolate the electrolyte, reduce the occurrence of side reactions, and improve the initial charge and discharge capacity of the material. However, the cycle performance of the positive electrode material is poor, and the gas production is also high, and the safety is low.
[0007] Therefore, how to effectively reduce the gas production of cobalt-free positive electrode materials during the cycle process and improve the safety performance of the battery is a technical problem that needs to be solved urgently. Summary of the invention
[0008] The object of the present invention is to provide a cobalt-free positive electrode material and its modification method and application. The present invention modifies the surface of the cobalt-free positive electrode material with amino groups, which can make the positive electrode surface have electron cloud polarization areas, that is, electron-dense areas and electron-deficient areas, providing a more convenient channel for the migration of lithium ions, and accelerating the formation of the SEI film on the surface of the initial cobalt-free positive electrode material to prevent the surface film from being oxidized. At the same time, after modification with amino groups, the decomposition potential of the traditional electrolyte in the cobalt-free battery is improved, and the stability of the electrolyte is also improved, and finally the cycle stability of the battery containing the cobalt-free positive electrode material provided by the present invention is improved, and the battery gas production during its cycle and the thermal stability of the battery are reduced.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a cobalt-free positive electrode material, wherein the surface of the cobalt-free positive electrode material is modified with an amino group, and the chemical formula of the cobalt-free positive electrode material is Li a Ni x Mn y O 2 , wherein 1<a<1.2, 0.2≤x≤0.95, x+y=1, for example, a can be 1.01, 1.03, 1.05, 1.08, 1.1, 1.13, 1.15, 1.18 or 1.19, etc., and x can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.95, etc.
[0011] The present invention modifies the surface of the cobalt-free positive electrode material with amino groups, and the amino groups can cause the positive electrode surface to have electron cloud polarization regions, that is, electron-dense regions and electron-deficient regions, thereby providing a more convenient channel for the migration of lithium ions and accelerating the formation of an SEI film on the surface of the initial cobalt-free positive electrode material to prevent the surface film from being oxidized. At the same time, after modification with amino groups, the decomposition potential of a traditional electrolyte in a cobalt-free battery is increased, and the stability of the electrolyte is further increased, thereby ultimately improving the cycle stability of a battery containing the cobalt-free positive electrode material provided by the present invention, reducing the gas production of the battery during its cycle, and reducing the thermal stability of the battery.
[0012] In the present invention, amino group (-NH 2 ) as a polar group can make the electron cloud polarized area on the positive electrode surface exist during the battery charging and discharging process, that is, there are electron-dense areas and electron-deficient areas, which provides a more convenient channel for the migration of lithium ions and can improve the overall fast charging performance of the battery to a certain extent; the amino-modified cobalt-free positive electrode material will accelerate the formation of the initial positive electrode surface SEI film and prevent the surface film from being oxidized, which helps to further reduce the battery gas production and improve the overall thermal stability of the battery to a certain extent; at the same time, the amino group (-NH 2 ) can improve the decomposition potential of traditional electrolytes. This is because the functionalized cobalt-free cathode material has a lower catalytic potential and thus a weaker catalytic activity than the material surface coated with a single metal oxide. Therefore, it can improve the decomposition potential of the electrolyte, so that the electrolyte still has good stability when the battery is charged and discharged at a high potential of 4.4V, thereby improving the cycle stability of the entire battery.
[0013] If other groups are selected for modification, such as hydroxyl groups, which are weak electron-withdrawing groups, it is difficult to form an electron cloud polarization region on the surface of the cobalt-free positive electrode material. The amino groups in the present invention have a strong ability to delocalize electrons in the cobalt-free positive electrode material modified with them, which can increase the reaction energy barrier with other ionic groups. The effect of reducing gas production and cycle stability during the battery cycle is more obvious than that of the hydroxyl-modified cobalt-free positive electrode material.
[0014] The cobalt-free positive electrode material provided by the present invention may be doped and / or coated with oxides, and preferably at least coated with oxides.
[0015] Preferably, the raw material containing the amino group is a silane coupling agent containing an amino group.
[0016] In the present invention, the silane coupling agent containing an amino group includes but is not limited to at least one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane or anilinemethyltriethoxysilane, preferably a diamino or polyamino structure.
[0017] In a second aspect, the present invention provides a method for modifying the cobalt-free positive electrode material as described in the first aspect, the modification method comprising:
[0018] The cobalt-free positive electrode material, the dispersant and the silane coupling agent containing the amino group are mixed and pyrolyzed to obtain the cobalt-free positive electrode material with the surface modified with the amino group;
[0019] Among them, the chemical formula of the cobalt-free positive electrode material is Li a Ni x Mn y O 2 , wherein 1<a<1.2, 0.2≤x≤0.95, x+y=1, for example, a can be 1.01, 1.03, 1.05, 1.08, 1.1, 1.13, 1.15, 1.18 or 1.19, etc., and x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.95, etc.
[0020] In the present invention, the surface of the cobalt-free positive electrode material is modified by a silane coupling agent containing an amino group, and the amino group is uniformly modified on the cobalt-free positive electrode material through a mixed pyrolysis process. The preparation method is simple and the amino group has strong adhesion.
[0021] In the present invention, the mixed pyrolysis process can be achieved by stirring or by adding in a dispersed manner in steps.
[0022] Preferably, the mass volume ratio of the cobalt-free positive electrode material to the silane coupling agent containing an amino group is 1:(1-10) kg / mL, for example, 1:1 kg / mL, 1:2 kg / mL, 1:3 kg / mL, 1:4 kg / mL, 1:5 kg / mL, 1:6 kg / mL, 1:7 kg / mL, 1:8 kg / mL, 1:9 kg / mL or 1:10 kg / mL, etc.
[0023] In the present invention, if the mass-to-volume ratio of the cobalt-free positive electrode material to the silane coupling agent containing an amino group is too small, that is, the amount of the silane coupling agent containing an amino group added is too much, there will be too much silane coupling agent on the surface, which reduces the conductivity of the cobalt-free positive electrode material. If the mass-to-volume ratio is too large, that is, the amount of the silane coupling agent containing an amino group added is too small, it is not conducive to the uniform modification of the amino group, resulting in the situation that there is no group modification on the surface of the cobalt-free positive electrode material, resulting in a decrease in the electrochemical performance of the cobalt-free positive electrode material.
[0024] Preferably, the mass concentration of the cobalt-free positive electrode material in the dispersant is 50-100 g / L, for example, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L or 100 g / L, etc.
[0025] In the present invention, if the mass concentration of the cobalt-free positive electrode material in the dispersant is too small, it will affect the cost and cause waste of the dispersant and the silane coupling agent. If the mass concentration is too large, it will cause the agglomeration of the cobalt-free positive electrode material to increase, which is not conducive to the uniform adhesion of the silane coupling agent.
[0026] Preferably, the dispersant comprises N,N-dimethylformamide.
[0027] Preferably, the volume ratio of the silane coupling agent containing an amino group to the dispersant is 10 -5 ~10 -4 , for example 1×10 -5 , 2×10 -5 , 3×10 -5 , 4×10 -5 , 5×10 -5 , 6×10 -5 ,7×10 -5 , 8×10 -5 ,9×10 -5 or 1×10 -4 wait.
[0028] Preferably, the temperature of the mixed pyrolysis is 120-180°C, for example, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C, etc.
[0029] In the present invention, if the temperature of the mixed pyrolysis is too low, the silane coupling agent cannot be completely pyrolyzed, resulting in the presence of surface fragment-like organic matter and the inability to achieve amino group modification. If the temperature of the mixed pyrolysis is too high, the amino group will be separated from the surface of the cobalt-free positive electrode material, so that the group does not modify the cobalt-free positive electrode.
[0030] Preferably, the mixed pyrolysis comprises:
[0031] The cobalt-free cathode material and the dispersant are first ultrasonically treated, and then a silane coupling agent containing an amino group is added and stirred, and the stirring process is accompanied by a thermal decomposition process.
[0032] In the present invention, ultrasound is first performed and then the silane coupling agent containing an amino group is added, so that more uniform mixing can be achieved.
[0033] Preferably, the stirring speed is 200-600 r / min, for example, 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 550 r / min or 600 r / min.
[0034] Preferably, the stirring time is 15 to 30 min, for example, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, etc.
[0035] Preferably, the pyrolysis temperature is 120-180°C, for example, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C, etc.
[0036] As a preferred technical solution, the modification method comprises:
[0037] First, the cobalt-free cathode material and the dispersant are ultrasonically treated, and then a silane coupling agent containing an amino group is added and stirred at a speed of 200 to 600 r / min for 15 to 30 minutes. The stirring process is accompanied by a thermal decomposition process at 120 to 180° C., so as to obtain a cobalt-free cathode material with an amino group modified on the surface;
[0038] Among them, the chemical formula of the cobalt-free positive electrode material is Li a Ni x Mn y O 2 , wherein 1<a<1.2, 0.2≤x≤0.95, x+y=1; the mass volume ratio of the cobalt-free positive electrode material to the silane coupling agent containing an amino group is 1:(1~10)kg / mL; the mass concentration of the cobalt-free positive electrode material in the dispersant is 50~100g / L; the volume ratio of the silane coupling agent containing an amino group to the dispersant is 10 -5 ~10 -4 .
[0039] In a third aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the cobalt-free positive electrode material as described in the first aspect.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The present invention modifies the surface of the cobalt-free positive electrode material with amino groups, and the amino groups can cause the positive electrode surface to have electron cloud polarization regions, that is, electron-dense regions and electron-deficient regions, thereby providing a more convenient channel for the migration of lithium ions and accelerating the formation of an SEI film on the surface of the initial cobalt-free positive electrode material to prevent the surface film from being oxidized. At the same time, after modification with amino groups, the decomposition potential of a traditional electrolyte in a cobalt-free battery is increased, and the stability of the electrolyte is further increased, thereby ultimately improving the cycle stability of a battery containing the cobalt-free positive electrode material provided by the present invention, reducing the gas production of the battery during its cycle, and reducing the thermal stability of the battery. The battery provided by the present invention has a capacity retention rate of more than 98.5% after 300 cycles at 1C at 25°C, a capacity retention rate of more than 95.1% after 600 cycles at 1C at 25°C, a capacity retention rate of more than 94.3% after 300 cycles at 1C at 60°C, and a capacity retention rate of more than 89.1% after 600 cycles at 1C at 60°C. After further adjusting the amount of amino-containing silane coupling agent added and the thermal decomposition temperature, the capacity retention rate of more than 99.3% after 300 cycles at 1C at 25°C, the capacity retention rate of more than 97.3% after 600 cycles at 1C at 25°C, the capacity retention rate of more than 96.1% after 300 cycles at 1C at 60°C, and the capacity retention rate of more than 91.7% after 600 cycles at 1C at 60°C. The gas production per Ah after the battery is cycled is as follows: the gas production after 300 cycles at 25°C is as low as 0.13 mL / Ah, the gas production after 600 cycles at 25°C is as low as 0.3 mL / Ah, the gas production after 300 cycles at 60°C is as low as 0.28 mL / Ah, and the gas production after 600 cycles at 60°C is as low as 0.45 mL / Ah. The preparation method provided by the present invention is simple, and the amino group has strong adhesion to the surface of the cobalt-free positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 N1s of the photoelectron spectroscopy (XPS) of the cobalt-free positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0044] In a specific embodiment, the present invention provides a method for preparing a cobalt-free positive electrode material, the preparation method comprising the following steps:
[0045] (1) Lithium salt (LiCO 3 and / or LiOH) and the precursor Ni x Mn 1-x (OH)2 (0.2≤x≤0.95) and the dopant are mixed uniformly by a high-speed mixer, the speed of the high-speed mixer is 2000-4000r / min, the mixing time is 10-20min, and the material is put into a box-type atmosphere furnace for sintering at a sintering temperature of 800-1000°C. After sintering, the material is crushed, and after crushing, the material is crushed by a jet mill, and a burnt material is obtained after crushing;
[0046] The dopant may be ZrO 2 、TiO 2 、TeO、TeO 2 , SbO 2 , Sb 2 O 3 , Y 2 O 3 、Bi 2 O 3 or 2 O 5 At least one of the above, the total doping amount of the dopant can be 1000ppm to 5000ppm, and the particle size D50 of the calcined material after airflow pulverization is 2.5 to 3.5μm;
[0047] (2) mixing the calcined material with the coating agent, and sintering at 500 to 900° C. for 5 to 12 hours to obtain a cobalt-free positive electrode material;
[0048] Wherein, the coating agent may be Al 2 O 3 、ZrO 2 、TiO 2 、TiO 2 , H 3 BO 3 、MgO、TeO、TeO 2 、ZnO、WB、WB 2 、TiN、TiC、Y 2 O 3 , Li 2 ZrO 3 or Li 2 TiO 3 At least one of the above-mentioned coating agents may have a total coating amount of 1500ppm to 5000ppm.
[0049] Example 1
[0050] This embodiment provides a cobalt-free positive electrode material. The surface of the cobalt-free positive electrode material is modified with amino groups. The chemical formula of the cobalt-free positive electrode material is Li 1.05 Ni 0.75 Mn 0.25 O 2 .
[0051] The modification method of the cobalt-free positive electrode material is as follows:
[0052] Take 1Kg of cobalt-free positive electrode material Li 1.05 Ni 0.75 Mn 0.25 O 2 Put it into 10L N,N-dimethylformamide, ultrasonicate for 20min, then add 1ml of γ-aminopropyltriethoxysilane (KH550) and stir while heating to 120°C, react for 15min, wash it with acetone and alcohol three times, put it in an oven to dry, and then sieve it to obtain the cobalt-free positive electrode material;
[0053] The cobalt-free cathode material Li 1.05 Ni 0.75 Mn 0.25 O 2 The preparation method of refers to the preparation method provided in the above specific embodiment:
[0054] Wherein, in step (1), 4.72 kg of LiOH and 10 kg of Ni 0.75 Mn 0.25 (OH) 2 and 12.83 g of Ta 2 O 5 The dopant was sintered at 950℃ for 10h, and the D50 of the fired material was 2.8μm;
[0055] In step (2), 10 kg of sintered material and 30.2 g of Al 2 O3 and 25.2g WO 3 , sintered at 725℃ for 5h.
[0056] Figure 1 The N1s of the photoelectron spectroscopy (XPS) of the cobalt-free cathode material prepared in Example 1 is shown. It can be seen from the figure that the surface of the cobalt-free cathode material is modified with amino groups (-NH 2 ) group.
[0057] Example 2
[0058] This embodiment provides a cobalt-free positive electrode material. The surface of the cobalt-free positive electrode material is modified with amino groups. The chemical formula of the cobalt-free positive electrode material is Li 1.05 Ni 0.75 Mn 0.25 O 2 .
[0059] The modification method of the cobalt-free positive electrode material is as follows:
[0060] Take 1Kg of cobalt-free positive electrode material Li 1.05 Ni0.75 Mn 0.25 O 2 Put it into 10L N,N-dimethylformamide, ultrasonicate for 20 minutes, then add 5ml of γ-aminopropyltriethoxysilane (KH550) and stir while heating to 150°C, react for 23 minutes, wash it three times with acetone and alcohol, put it in an oven to dry, and then sieve it to obtain the cobalt-free positive electrode material;
[0061] The preparation method is consistent with that in Example 1.
[0062] Example 3
[0063] This embodiment provides a cobalt-free positive electrode material. The surface of the cobalt-free positive electrode material is modified with amino groups. The chemical formula of the cobalt-free positive electrode material is Li 1.1 Ni 0.56 Mn 0.44 O 2 .
[0064] The modification method of the cobalt-free positive electrode material is as follows:
[0065] Take 1Kg of cobalt-free positive electrode material Li 1.1 Ni 0.56 Mn 0.44 O 2 Put it into 10L N,N-dimethylformamide, ultrasonicate for 20min, then add 10ml of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane (KH-602) and stir while heating to 180°C, react for 30min, wash it with acetone and alcohol three times, put it in an oven to dry, and then sieve it to obtain the cobalt-free positive electrode material;
[0066] Cobalt-free cathode material Li 1.1 Ni 0.56 Mn 0.44 O 2 The difference between the preparation method of and Example 1 is:
[0067] In step (1), 4.48 kg of Li 2 CO 3 and 10Kg of Ni 0.56 Mn 0.44 (OH) 2 .
[0068] Example 4
[0069] The difference between this embodiment and embodiment 1 is that the amount of KH550 added in this embodiment is 15 mL, that is, Li 1.05 Ni 0.75 Mn 0.25 O 2The mass volume ratio with KH550 is 1:15kg / mL.
[0070] The remaining modification methods, preparation methods and parameters were consistent with those in Example 1.
[0071] Example 5
[0072] The difference between this embodiment and embodiment 1 is that the temperature of stirring pyrolysis in this embodiment is 100°C.
[0073] The remaining modification methods, preparation methods and parameters were consistent with those in Example 1.
[0074] Example 6
[0075] The difference between this embodiment and embodiment 1 is that the temperature of stirring pyrolysis in this embodiment is 200°C.
[0076] The remaining modification methods, preparation methods and parameters were consistent with those in Example 1.
[0077] Comparative Example 1
[0078] The difference between this comparative example and Example 1 is that in this comparative example, the functional groups of the cobalt-free positive electrode material are not modified, and in the preparation method, no coating is performed, only doping is performed.
[0079] The rest of the preparation methods and parameters were the same as those in Example 1.
[0080] Comparative Example 2
[0081] The difference between this comparative example and Example 1 is that in this comparative example, the functional group of the cobalt-free positive electrode material is not modified, that is, the cobalt-free positive electrode material Li in this comparative example is not treated by the modification method. 1.05 Ni 0.75 Mn 0.25 O 2 .
[0082] No modification method was performed.
[0083] The rest of the preparation methods and parameters were the same as those in Example 1.
[0084] Comparative Example 3
[0085] Take 1Kg of cobalt-free positive electrode material Li 1.05 Ni 0.75 Mn 0.25 O 2 Put it into 10L N,N-dimethylformamide, ultrasonicate for 20min, then add 10mL of 3-hydroxy-1,2-propylene oxide and stir while heating to 90°C. After reacting for 2h, wash it three times with methanol, put it in an oven to dry, and then sieve it to obtain a hydroxyl (-OH) modified cobalt-free positive electrode material;
[0086] The remaining preparation methods and parameters were consistent with those in Example 1. The cobalt-free positive electrode materials provided in Examples 1-6 and Comparative Examples 1-2 were mixed with polyvinylidene fluoride, carbon black, and NMP (N-methylpyrrolidone) in a ratio of 92:4:4 and then coated on aluminum foil to prepare a positive electrode sheet, and a metal lithium sheet was used as a counter electrode to obtain a button half-cell, and the electrochemical performance test was performed:
[0087] The test conditions are: charge and discharge cycles are performed at 25°C and 60°C at a charge and discharge current of 1C. The results are shown in Table 1.
[0088] Table 1
[0089]
[0090]
[0091] Table 2 shows the gas production (mL) per Ah of the batteries provided in Examples 1-6 and Comparative Examples 1-2 after cycling.
[0092] Table 2
[0093]
[0094]
[0095] Combining Table 1 and Table 2:
[0096] From the data results of Example 1 and Example 4, it can be seen that adding too much amino-containing silane coupling agent will lead to an incomplete pyrolysis process, resulting in the silane coupling agent adhering to the surface not being completely converted into amino groups, resulting in poor cycle stability.
[0097] From the data results of Example 1 and Examples 5 and 6, it can be seen that the temperature in the pyrolysis reaction is too low, which is not conducive to the complete decomposition of the silane coupling agent into amino groups, resulting in the inability to complete the modification of the amino groups on the surface. If the temperature is too high, the formed amino groups will not be able to adhere to the surface of the cobalt-free positive electrode material in the early stage of formation, so that the amino groups cannot be completely coated on the surface of the cobalt-free positive electrode material.
[0098] From the data results of Example 1 and Comparative Example 1, it can be seen that the cobalt-free positive electrode material that has not been coated or modified with the amino group in the present invention has poor cycle stability and comes into contact with the electrolyte during the cycle, resulting in increased gas production and poor battery cyclability.
[0099] It can be seen from the data results of Example 1 and Comparative Example 2 that compared with the conventional method of reducing gas production by oxide coating, the cobalt-free positive electrode material in the present invention is more effective in reducing gas production and cycle stability during the battery cycle after being modified with amino groups.
[0100] From the data results of Example 1 and Comparative Example 3, it can be seen that compared with the cobalt-free positive electrode material modified with the weak electron-withdrawing group hydroxyl (-OH), the amino-modified cobalt-free positive electrode material in the present invention has a stronger ability to delocalize electrons, can increase the reaction energy barrier with other ionic groups, and is more effective in reducing gas production and cycle stability during the battery cycle than the hydroxyl-modified cobalt-free positive electrode material.
[0101] From the data results in Table 1 and Table 2, it can be seen that the cobalt-free positive electrode material provided by the present invention, after surface modification with amino groups, not only effectively reduces the gas production of the battery under normal temperature cycle, but also greatly reduces the gas production of the battery under high temperature cycle, thereby improving the thermal stability of the battery. Under high temperature conditions, the molecular movement is accelerated, which promotes the rapid conversion of the electrolyte. Since the gas production process is a weakly reversible process, the modification of the amino group increases the reaction potential, thereby causing the reaction to proceed in the direction of non-gas production, thereby reducing high temperature gas production and improving cycle stability.
[0102] In summary, the present invention modifies the surface of the cobalt-free positive electrode material with amino groups, and the amino groups can make the positive electrode surface have electron cloud polarization regions, that is, electron-dense regions and electron-deficient regions, providing a more convenient channel for the migration of lithium ions, and accelerating the formation of the initial cobalt-free positive electrode material surface SEI film to prevent the surface film from being oxidized. At the same time, after modification with amino groups, the decomposition potential of the traditional electrolyte in the cobalt-free battery is improved, and the stability of the electrolyte is also improved, and finally the cycle stability of the battery containing the cobalt-free positive electrode material provided by the present invention is improved, and the battery gas production during its cycle is reduced, as well as the thermal stability of the battery. And the preparation method provided by the present invention is simple, and the amino group has strong adhesion to the surface of the cobalt-free positive electrode material. The battery provided by the present invention has a capacity retention rate of more than 98.5% after 300 cycles at 1C at 25°C, a capacity retention rate of more than 95.1% after 600 cycles at 1C at 25°C, a capacity retention rate of more than 94.3% after 300 cycles at 1C at 60°C, and a capacity retention rate of more than 89.1% after 600 cycles at 1C at 60°C. After further adjusting the amount of amino-containing silane coupling agent added and the thermal decomposition temperature, the capacity retention rate of more than 99.3% after 300 cycles at 1C at 25°C, the capacity retention rate of more than 97.3% after 600 cycles at 1C at 25°C, the capacity retention rate of more than 96.1% after 300 cycles at 1C at 60°C, and the capacity retention rate of more than 91.7% after 600 cycles at 1C at 60°C. The gas production per Ah of the battery after cycling is as follows: the gas production after 300 cycles at 25°C is as low as below 0.13mL / Ah, the gas production after 600 cycles at 25°C is as low as below 0.3mL / Ah, the gas production after 300 cycles at 60°C is as low as below 0.28mL / Ah, and the gas production after 600 cycles at 60°C is as low as below 0.45mL / Ah.
[0103] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for modifying a cobalt-free positive electrode material, characterized in that: The surface of the cobalt-free positive electrode material is modified with amino groups. The chemical formula of the cobalt-free positive electrode material is Li a Ni x Mn y O2, where 1<a<1.2, 0.2≤x≤0.95, x+y=1; The modification method comprises: First, the cobalt-free cathode material and the dispersant are ultrasonically treated, and then a silane coupling agent containing an amino group is added and stirred, and the stirring process is accompanied by a thermal decomposition process to obtain a cobalt-free cathode material with an amino group modified on the surface; The cobalt-free positive electrode material contains oxide doping and / or coating; the doped oxide includes at least one of ZrO2, TiO2, TeO, TeO2, SbO2, Sb2O3, Y2O3, Bi2O3 or Ta2O5; the coated oxide includes at least one of Al2O3, ZrO2, TiO2, H3BO3, MgO, TeO, TeO2 or ZnO; The silane coupling agent containing an amino group includes at least one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane or anilinemethyltriethoxysilane; The mass volume ratio of the cobalt-free positive electrode material to the silane coupling agent containing an amino group is 1: (1-10) kg / mL; The pyrolysis temperature is 120-180°C.
2. The method for modifying a cobalt-free positive electrode material according to claim 1, characterized in that: The mass concentration of the cobalt-free positive electrode material in the dispersant is 50-100 g / L.
3. The method for modifying a cobalt-free cathode material according to claim 1, characterized in that: The volume ratio of the silane coupling agent containing an amino group to the dispersant is 10 -5 ~10 -4 .
4. The method for modifying a cobalt-free positive electrode material according to claim 1, characterized in that: The dispersant includes N,N-dimethylformamide.
5. The method for modifying a cobalt-free positive electrode material according to claim 1, characterized in that: The stirring speed is 200-600 r / min.
6. The method for modifying a cobalt-free cathode material according to claim 1, characterized in that: The stirring time is 15 to 30 minutes.
7. The method for modifying a cobalt-free cathode material according to claim 1, characterized in that: The modification method comprises: First, the cobalt-free cathode material and the dispersant are ultrasonically treated, and then a silane coupling agent containing an amino group is added and stirred at a speed of 200-600 r / min for 15-30 min. The stirring process is accompanied by a thermal decomposition process at 120-180° C., thereby obtaining a cobalt-free cathode material with an amino group modified on the surface. Among them, the chemical formula of the cobalt-free positive electrode material is Li a Ni x Mn y O2, wherein 1<a<1.2, 0.2≤x≤0.95, x+y=1; the mass volume ratio of the cobalt-free positive electrode material to the silane coupling agent containing an amino group is 1:(1~10)kg / mL; the mass concentration of the cobalt-free positive electrode material in the dispersant is 50~100g / L; the volume ratio of the silane coupling agent containing an amino group to the dispersant is 10 -5 ~10 -4 .
8. A cobalt-free positive electrode material, characterized in that: The cobalt-free positive electrode material is prepared by the modification method according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the cobalt-free positive electrode material as claimed in claim 8.
Citation Information
Patent Citations
Cobalt-free cathode material, preparation method thereof, lithium ion battery cathode and lithium battery
CN111916697A
Positive electrode composite material and preparation method and application thereof
CN112186158A
Positive pole piece and lithium ion battery comprising same
CN112786834A
Nonaqueous electrolyte battery
CN103094607A